Exploring the Therapeutic Potential of Musa paradisiaca L. Pith: A Study on Antioxidant, Cytotoxic, Membrane Stabilizing and Thrombolytic Activities (Bangladesh Pharmaceutical Journal, 2025)
Musa paradisiaca L. has been utilized for a considerable amount of time in the practice of folk therapies across different cultures, particularly in India. The many components of the plant, including its leaves, roots, and blossoms, are utilized to cure a vast number of conditions, including cough, bronchitis, dysmenorrhea, and menorrhagia. This study investigates the pharmacological potential of different fractions derived from the pith of M. paradisiaca, focusing on their antioxidant, cytotoxic, membranestabilizing, and anti-thrombolytic activities. The ethyl acetate soluble fraction (EASF) exhibited the highest antioxidant activity, with an IC50 value of 18.53 μg/ml, which strongly correlated with its phenolic content. The crude methanol extract (CME) demonstrated remarkable cytotoxicity, with an LC50 of 19.91 μg/ml, and significant membrane-stabilizing effects, comparable to aspirin, reducing hemolysis by 74.92% in heat-induced and 44.05% in hypotonic-induced conditions. Moreover, the aqueous and dichloromethane fractions (AQSF and DCMSF) showed promising anti-thrombotic properties, inhibiting clot formation by 28.87% and 20.95%, respectively. These results indicate that, the pith fractions of M. paradisiaca possess diverse bioactive properties, particularly CME and EASF, making them promising candidates for developing novel therapeutic agents. Further research is required to isolate the bioactive compounds as well as elucidate their mechanisms of action.Bangladesh Pharmaceutical Journal 28(2): 193-202, 2025 (July)